(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The antioxidant efficacy of aqueous extracts of twelve plants of the Asteraceae family, which is from natural flora, was investigated by the method of scavenging free radicals of the compound Diphenylpicrylhydrazyl (DPPH) namely Aster subulatus, Calendula officinalis, Carduus pycnocephalus, Carthamus Oxantea, and Carthamus Oxantea. linearis, Launaea nudicaulis, Sonchus maritimus and Sonchus oleraceus, this activity is compared to an inhibition ratio (IC50) half of the maximum inhibitor concentration of 50 of the standard ascorbic acid (vitamin C) antioxidant. the most effective of which was Carhamus oxyacantha, which reached 68.430% and Centaurea pallescens 66.432%, and the lowest effectiveness in, Launaea nudicaulis was 40.430% and Koelpinia linearis was 43.816%. The mineral elements were analyzed in the aerial part of plants : (K, Na, , Mg, Ca, and P) using Atomic absorption (Spectrophotometer apparatus 5000 (Atomic) - the results showed that plants contain very good ratios of elements as the best plant in terms of content was Carduus pycnocephalus and Carthamus oxykontha.